Analysis of commute characteristics and residential location of IIUM Gombak campus employees of Malaysia - Mohit, Mohammad Abdul; Mustafa, Mootaz Munjid (2008)
Higher learning institutions, particularly universities, are important nodes which can help in decentralizing the monocentric stigma of urban areas by encouraging employment and housing growth in metropolitan areas. The case study Gombak Campus of International Islamic University Malaysia (HUM), located 15 kilometers to the north-west of Kuala Lumpur City, is currently an employment node in the Klang Valley region. -Being a node of employment, it is expected that it will generate residential development in the vicinity 'of its location by supporting the determining two factors of residential location - commuting cost and rent. Although there are certain truths that rent and commute cost are important determinants in residential location, other factors also influence residential location decision making. This paper, therefore, attempts to identify an array of factors and the extent to which these factors influence commute and residential attributes of the employees of IIUM Gombak Campus. Findings of this study reveal that there is a significant relationship between commute behavior and residential characteristics and a number of other factors normally overlooked by the mainstream residential location models.